Asymmetric Michael Addition Mediated by Chiral Ionic Liquids - Suzuki, Yumiko (Mini-Reviews in Organic Chemistry, 2018)
Chiral ionic liquids with a focus on their applications in asymmetric Michael additions and related reactions were reviewed. The examples were classified on the basis of the mode of asymmetric induction (e.g., external induction/non-covalent interaction or internal induction/covalent bond formation), the roles in reactions (as a solvent or catalyst), and their structural features (e.g., imidazolium-based chiral cations, other chiral oniums; proline derivatives). Most of the reactions with high chiral induction are Michael addition of ketones or aldehydes to chalcones or nitrostyrenes where proline-derived chiral ionic liquids catalyze the reaction through enamine/ iminium formation. Many reports demonstrate the recyclability of ionic liquid-tagged pyrrolidines.
Keywords: imidazole ionic liquid